1224. Drug-Resistance Dynamics of Staphylococcus aureus at a Tertiary Hospital, Beijing, China: 2013–2017. (26th November 2018) - Zhang, Yuzheng; Johnston, Janice Mary; Fu, Qiang
Abstract: Background: To understand the drug-resistance dynamics of Staphylococcus aureus and provide references for effective control of methicillin-resistant Staphylococcus aureus (MRSA) infection. Methods: All data were obtained from the healthcare-associated infection surveillance system. Different strains of S. aureus were identified using the VITEK-2 automated system, the drug susceptibility results of resistance and intermediate were classified into resistance. Chi-square test and variation analyses of S. aureus drug-resistant rate were performed. Results: From 2013 to 2017, 2, 289 strains of S. aureus were isolated, and the specimen were mostly collected from sputum (721, 31.50%), wound secretion (211, 9.22%), and blood (210, 9.17%). The resistance rate of S. aureus was highest for tigecycline (94.43% in 2013, 100% in 2017) and penicillin (96.49% in 2013, 95.60% in 2017) ( P = 0.028). The resistance rates among other drugs such as clindamycin (65.28% in 2013, 71.39% in 2017) and erythromycin (69.62% in 2013, 62.59% in 2017) were more stable ( P = 0.056). However, oxacillin (from 73.68% to 34.47%), gentamicin (from 51.51% to 24.13%), and tetracycline (from 46.78% to 30.81%) showed a declining trend ( P = 0.017). Meanwhile, there were almost no S. aureus resistance to linezolid, vancomycin, and nitrofurantoin. During the previous 5-year period, MRSA rates decreased sharply and in 2017 rate was 34.47%. In 2017, MRSA was most frequently isolated in orthopedics, emergency ICU, and respiratory. Conclusion: The reduction in drug-resistant MRSA may be evidence of effective antibiotic administration practice. Whereas more comprehensive infection control measures are needed to prevent the transmission of S. aureus and MRSA. Disclosures: All authors: No reported disclosures.